Association of iron status indicators with thyroid hormone concentrations during pregnancy: a systematic review and meta-analysis - Parsaei, Mohammadamin; Dashtkoohi, Mohadese; Amirkhalili, Elahe; Chashmyazdan, Mohammadreza; Korevaar, Tim I. M.; Nazeri, Pantea (Frontiers in Endocrinology, 2025)
BackgroundMaternal thyroid hormones play a vital role in fetal development, and imbalances can lead to adverse outcomes. Iron deficiency may impair thyroid function due to iron’s essential role in iodine oxidation during thyroid hormone synthesis. This review examines the relationship between various indicators of maternal iron status and thyroid function during pregnancy.MethodsWe conducted a systematic search in MEDLINE/PubMed, Web of Science, Embase, Scopus, and the Cochrane Library for studies published up to 2023. Meta-analyses determined pooled thyroid hormone levels in patients with and without iron deficiency, using serum ferritin (cut-off = 30 µg/L) and hemoglobin (cut-off = 11 g/dL). Meta-regression analyses examined linear relationships between iron status indicators and thyroid hormones.ResultsForty-seven studies involving 53,152 pregnant women were included. Meta-analysis showed no significant difference in thyroid-stimulating hormone, free T4, or total T4 when considering serum ferritin levels in iron-deficient versus iron-sufficient individuals. However, regarding hemoglobin levels, iron deficiency was associated with higher thyroid-stimulating hormone (2.31 mIU/L vs. 1.75 mIU/L) and lower free T4 (10.7 pmol/L vs. 13.3 pmol/L), but not total T4. Meta-regression revealed no significant associations between serum ferritin and thyroid hormones. Conversely, maternal hemoglobin levels were inversely associated with thyroid-stimulating hormone (P-value = 0.009) and directly associated with free T4 (P-value < 0.001), with no significant link to total T4.ConclusionsMaternal hemoglobin levels are more strongly correlated with thyroid function than serum ferritin levels. This suggests that monitoring hemoglobin could enhance the early detection and management of thyroid dysfunction during pregnancy.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO, identifier CRD4202451820.